2009
DOI: 10.2166/wst.2009.016
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic water disinfection of Cryptosporidium parvum and Giardia lamblia using a fibrous ceramic TiO2 photocatalyst

Abstract: Cryptosporidium parvum and Giardia lamblia are two of the most chlorine resistant microorganisms with notable adverse effects on humans. Our study shows that waters containing these two protozoa at low concentrations can be efficiently disinfected in continuous flow by using a commercial fibrous ceramic TiO(2) photocatalyst. The efficiency of the photocatalytic disinfection is largely enhanced by adding a small concentration of chlorine. In this way, the residence time on the photoreactor can be considerably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…García et al. demonstrated that water containing these two protozoans at low concentrations could be efficiently disinfected in continuous flow by using commercial fibrous ceramic TiO 2 photocatalysts . The efficiency of photocatalytic disinfection is largely enhanced by adding a small concentration of chlorine.…”
Section: Photocatalytic Use Of Tio2 Nanomaterials In Aqueous and Biolmentioning
confidence: 99%
“…García et al. demonstrated that water containing these two protozoans at low concentrations could be efficiently disinfected in continuous flow by using commercial fibrous ceramic TiO 2 photocatalysts . The efficiency of photocatalytic disinfection is largely enhanced by adding a small concentration of chlorine.…”
Section: Photocatalytic Use Of Tio2 Nanomaterials In Aqueous and Biolmentioning
confidence: 99%
“…where ε m and ε s are the relative dielectric constants of the membrane and the solution respectively. Equations (32) and (33) can be solved numerically after applying the appropriate boundary conditions [117,119,120] to yield the electric potential profile across a cell membrane.…”
Section: Figure 12: Schematic Of Bacteria-water Interface [113]mentioning
confidence: 99%
“…The electrostatic surface potential of the catalyst is defined by Equation (20). In like manner, the surface potential profile of the cells is defined by Equations (32) and (33). Under the pH conditions of interest (6 to 8, i.e., mostly neutral) and low electrolyte concentration, the TiO 2 surface is dominated by noncharged surface hydroxylated species, while the cell surface is mostly negative.…”
Section: Theoretical Model Formulationmentioning
confidence: 99%
“…Comparison should also be carried out with Legionella, Cryptosporidium, and Giardia lamblia, since previous studies found that these organisms are highly resistant to traditional disinfection practices [37]. Experimental work in this regard was in fact conducted in 2009 by Navalon et al and demonstrated that waters containing Cryptosporidium parvum and Giardia lamblia at low concentrations can be efficiently disinfected in continuous flow by using a commercial fibrous ceramic TiO 2 photocatalyst [38].…”
Section: Analysis Of Photocatalysis-mediated Antimicrobial Activitymentioning
confidence: 99%